A intertextualidade em livros didáticos do 9º ano do ensino fundamental - Silva, Gutemberg Lima da (2015)
Intertextuality is a cognitive, textual and discursive mechanism for the construction of interactional relationships, being used by several lines of work of the social sciences, in the construction and analysis of speeches. The more elaborate and precise the use of intertext, more command of the language the subject demonstrates , deserving, therefore, attention and study to understand this phenomenon. In this dissertation, we discuss the criterion of intertextuality as a constitutive element of the text, from the perspective of social interactionism. However, does the Portuguese language teaching pays attention to this phenomenon? would the textbooks of the Portuguese language address insufficiently or not this issue in the proposed activities to students,? The objective of the research is to investigate intertextuality, based on the analysis of the proposed activities to students in textbooks of the Portuguese Language, in 9th grade. In this dissertation, we discuss the criterion of intertextuality as a constitutive element of the text from the perspective of Social Interactionism. For this, We work with the notion of text by Beaugrande (1997), which is based on three constitution of actions taken in a given communicative event: social, cognitive and linguistic. We also work with the theoretical framework of intertextuality from the Textual Linguistics in Koch (2003, 2004, 2006, 2007, 2009, 2011) and Koch, Bentes and Cavalcante (2007). The objective of the research is to investigate the intertextuality in textbooks of Portuguese Language in 9th grade. Thus, the corpus consists of two textbooks, selected among those approved by the PNLD 2014, by which, quantitatively, chalked up the learning opportunities of intertextuality by categorization stricto sensu - explicit , theme, stylistic and implicit intertextuality - and qualitatively, it analyzes how these learning opportunities of intertextuality are addressed in the book. The results show that the use of intertextuality still holds the aspect of explicit category, basically the direct, indirect and free indirect speeches processes, and thematic intertextuality. The implicit and stylistic intertextuality, in turn, are not covered in the textbooks studied. It is noticed that the intertextuality of learning opportunities are more numerous in reading education axis, with little evidence in the teaching axis of text production. In respect to the axis of Oralidade, no learning opportunities occurrences were found in the analyzed books. The results provide the basis for discussions on the teaching of intertextuality in the Portuguese language classes in schools, showing a change of perspective in attention to this phenomenon in class.